Discrete but variable structure of animal societies leads to the false perception of a social continuum. Issue 5 (May 2016) - Rubenstein, Dustin R.; Botero, Carlos A.; Lacey, Eileen A.
Abstract : Animal societies are typically divided into those in which reproduction within a group is monopolized by a single female versus those in which it is shared among multiple females. It remains controversial, however, whether these two forms of social structure represent distinct evolutionary outcomes or endpoints along a continuum of reproductive options. To address this issue and to determine whether vertebrates and insects exhibit the same patterns of variation in social structure, we examined the demographic and reproductive structures of 293 species of wasps, ants, birds and mammals. Using phylogenetically informed comparative analyses, we found strong evidence indicating that not all reproductive arrangements within social groups are viable in nature and that in societies with multiple reproductives, selection favours instead taxon-specific patterns of decrease in the proportion of breeders as a function of group size. These outcomes suggest that the selective routes to sociality differ depending upon whether monopolization of reproduction by one individual is possible and that variation within and among taxonomic groups may lead to the false perception of a continuum of social structures. Thus, the occurrence of very large societies may require either complete reproductive monopolization (monogyny/singular breeding) or the maintenance of a taxon-specific range of values for the proportional decrease in the number of breeders within a group (polygyny/plural breeding), both of which may reduce reproductive conflict among females.